Pengaruh Pembelajaran Akuntansi Berkarakter, Minat Dan Motivasi Belajar Terhadap Prestasi Belajar Mahasiswa Akuntansi (Studi Kasus Pada Universitas Victory Sorong) - Ferdinando Solissa; Putu Anggreyani Widya Astuty (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This study aims to examine the effect of learning accounting character, interest, and learning motivation on learning achievement of accounting students at the University of Victory Sorong. The research was carried out on all students of the Accounting Study Program of the Faculty of Economics and Business, University of Victory Sorong. The data collection method used in this study is a survey method through distributing questionnaires. The sampling technique used was saturated sampling method. Students as the unit of analysis participated as many as 83 students. Data analysis used multiple linear regression with the help of the application of Statistical Package for The Social Science version 22. The results showed that the character of accounting learning, interest, and learning motivation had a positive and significant effect on learning achievement of accounting students.